Changes in physicochemical properties of mangrove sediments under Amazonian climatic regime - Berrêdo, José Francisco; Costa, Marcondes Lima da; Vilhena, Maria do Socorro P.; Matos, Christiene R. L. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The continuous and progressive maturation of mangrove sediments distributed along the estuary of the Marapanim River on the northeastern coast of Pará state was described based on their physicochemical properties (pH, Eh, and interstitial salinity), in order to demonstrate the influence of short but remarkable climate fluctuations on that sector of the Pará coast. Salinity patterns resulted from surface fluxes, concentrated by evaporation processes, diluted by the tides and the strong and prolonged rains in the region. Reducing conditions (-200 < Eh < -400 mV) are found in lower sediments, clayey, and rich in organic matter. In contrast, periods of drought have promoted oxidation and desiccation of the topographically higher sediment, resulting in a decrease of pH (3.5 to 4.5), and inverse relations between Eh and pH. The changes in physical and chemical gradients are in close association with the climate, the cycle of the tides, the movement of interstitial water, determining the degree of development and vertical and lateral differentiation of sediment and the distribution of vegetation in estuary.